The features of valve-preserving intervention in a malignant tumor of the right ventricle of heart - R.M. Vitovskiy; V.V. Isaіenko; O.A. Pishchurin; V.F. Onishchenko; I.V. Martyshchenko; D.М. Dyadyun; V.V. Grabarchuk (Кардіохірургія та інтервенційна кардіологія)
The article presents an unusual case of a metastatic lesion of the right ventricle with malignant neoplasm. Its nature and size was definitively determined during the operation. The surgical treatment of this lesion by valve-preserving operation on the tricuspid valve is discussed. Since 1970, surgical treatment of 62 patients with various types and localization of malignant heart tumors was performed, corresponding to 6.8 % of 912 patients with cardiac tumors. This case is an unusual example of secondary damage to the malignant tumor of the right ventricle. Its primary focus was seminoma (low-grade embryonic G3 cancer). Metastatic malignant tumors of the heart affect its walls, but may also spread to valve structures, requiring correction of valvular lesions. During surgical removal of the tumor it is necessary, as far as possible, to preserve valvular and sub-valvular structures in order to avoid valve prosthetics.